A novel green and eco-friendly synthesis of nickel oxide nanoparticles by auto combustion technique using allium cepa bulb extract and their dielectric behaviour - Sahila, S.; Prabhu, N.; Simiyon, G. Gnanamani; Jayakumari, L.S. (Chemical Data Collections, 2022)
•The synthesis of nickel oxide nanoparticles was achieved through eco friendly green method.•This synthetic method is found to be cost effective and economically viable.•The synthesized nano particles possess higher dielectric constant.•The minimum dielectric loss was observed with these nanoparticles.•These nanoparticles can be serving as a promising materials for capacitor applications. The green synthesis of nickel oxide nanoparticles using allium cepa bulb extract, is reported as cost effective, environmentally benign method which yields higher dielectric constant. The dielectric properties are studied as a function of frequency with various concentrations of nickel oxide nanoparticles using LCR meter and dielectric constant is found to decrease with the increase in frequency and large dielectric constant of about 1275 has been achieved for NiO-40 with minimum dielectric loss of 1.24 at 1 MHz. [Display omitted]